PENGARUH KOMPENSASI TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI PADA PUSAT KESEHATAN MASYARAKAT (PUSKESMAS) KECAMATAN PATANI UTARA - Fatni Taha; Abdullah W Jabid (Jurnal Manajemen Sinergi, 2022)
ABSTRACTObjective: The purpose of this study was to determine and analyze: the positive effect of compensation on job satisfaction; the positive effect of compensation on employee performance; and the effect of compensation on employee performance mediated by job satisfaction at the Community Health Center North Patani DistrictThe number of research samples is 78 respondents. The data analysis technique used in this study is SEM analysis using Smart Partial Least Square (PLS) as a statistical test tool.Methodology: The analytical model used are Structural Equation Modeling with SMART PLS as tools for the statistical test. Data collection tools used are questionnaires and interviews, and the number of respondents was 78 employee.Finding: H1, H2, and H4 are rejected, while H3 no accepted at the 5% confidence level. The results of the mediation test show that the t-statistic value of 2.019 is greater than the t-table of 1.96 and the p-value of 0.044 alpha (Î±) value of 5% (0.05).Conclusion: The results of this study indicate that: Compensation has a positive and significant effect on job satisfaction; Job satisfaction has a positive and significant effect on employee performance; Compensation has no positive and significant effect on employee performance; and satisfaction fully mediates the effect of compensation on employee performance.